Vitis vinifera root and leaf metabolic composition during fruit maturation: implications of defoliation. Issue 4 (21st September 2017) - Rossouw, Gerhard C.; Orchard, Beverley A.; Šuklje, Katja; Smith, Jason P.; Barril, Celia; Deloire, Alain; Holzapfel, Bruno P.
Abstract : Grapevine ( Vitis vinifera ) roots and leaves represent major carbohydrate and nitrogen (N) sources, either as recent assimilates, or mobilized from labile or storage pools. This study examined the response of root and leaf primary metabolism following defoliation treatments applied to fruiting vines during ripening. The objective was to link alterations in root and leaf metabolism to carbohydrate and N source functioning under conditions of increased fruit sink demand. Potted grapevine leaf area was adjusted near the start of véraison to 25 primary leaves per vine compared to 100 leaves for the control. An additional group of vines were completely defoliated. Fruit sugar and N content development was assessed, and root and leaf starch and N concentrations determined. An untargeted GC/MS approach was undertaken to evaluate root and leaf primary metabolite concentrations. Partial and full defoliation increased root carbohydrate source contribution towards berry sugar accumulation, evident through starch remobilization. Furthermore, root myo ‐inositol metabolism played a distinct role during carbohydrate remobilization. Full defoliation induced shikimate pathway derived aromatic amino acid accumulation in roots, while arginine accumulated after full and partial defoliation. Likewise, various leaf amino acids accumulated after partial defoliation. These results suggest elevated root and leaf amino N source activity when leaf N availability is restricted during fruit ripening. Overall, this study provides novel information regarding the impact of leaf source restriction, on metabolic compositions of major carbohydrate and N sources during berry maturation. These results enhance the understanding of source organ carbon and N metabolism during fruit maturation.